PREPARATION AND CHARACTERIZATION OF TRANSPARENT CONDUCTIVE ZnO THIN FILMS BY DC MAGNETRON SPUTTERING - Sudjatmoko Sudjatmoko; Suryadi Suryadi; Widdi Usada; Tono Wibowo; Wiryoadi Wiryoadi (GANENDRA Majalah IPTEK Nuklir, 2002)
PREPARATION AND CHARACTERIZATION OF TRANSPARENT CONDUCTIVE ZnO THIN FILMS BY DC MAGNETRON SPUTTERING. Transparent and conductive aluminium-doped zinc oxide thin films have been prepared by dc magnetron sputtering using targets composed of ZnO and Al2O3. Polycrystalline ZnO:Al films were deposited onto a heated glass substrate. The surface morphology and crystalline structure, as well as optical and electrical properties of the deposited films were found to depend directly on substrate temperature. From optical and electrical analysis were observed that the optical transmittance and conductivity of the ZnO:Al transparent conductive oxide films increased when deposition temperature was raised from 200 to 400 oC. Films grown on 300 oC substrates showed a high conductivity value of 0.2 x 102 -1cm-1 and a visible transmission of about 85%. The growth temperatures of 300 oC, aluminium doping levels of 0.9 wt.% were preferable to achieve ZnO:Al films with optical and structural qualities as required for solar cell applications.